The Aplysia Mytilus Inhibitory Peptide-Related Peptides: Identification, Cloning, Processing, Distribution, and Action - Fujisawa, Y. (J Neurosci, 1999)
Neuropeptides are a ubiquitous class of signaling molecules. In our attempt to understand the generation of feeding behavior inAplysia, we have sought to identify and fully characterize the neuropeptides operating in this system. Preliminary evidence indicated that Mytilus inhibitory peptide (MIP)-like peptides are present and operating in the circuitry that generates feeding in Aplysia. MIPs were originally isolated from the bivalve mollusc Mytilus edulis, and related peptides have been identified in other invertebrate species, but no precursor has been identified. In this study, we describe the isolation and characterization of novel AplysiaMIP-related peptides (AMRPs) and their precursor. Several AMRPs appear to have some structural and functional features similar to vertebrate opioid peptides. We use matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to confirm that all 14 AMRPs predicted by the precursor are processed in isolated neurons. Northern analysis, whole-mount in situ hybridization, and immunohistochemistry are used to map the abundant expression of these peptides in the CNS and peripheral tissues such as the digestive tract, vasculature, and the reproductive organs. Physiological studies demonstrate that the rank order of the inhibitory actions of these peptides is different for three target muscles. These results underscore the importance of using a multidisciplinary approach to identifying and characterizing the actions of neuropeptides in an effort to gain understanding of their role in systems of interest. The widespread distribution of the AMRPs indicates that they may be operating in many different systems of Aplysia.